Interstitial lung disease in patients treated with Cyclin-Dependent Kinase 4/6 inhibitors: A systematic review and meta-analysis of randomized controlled trials. (April 2022) - Zhang, Yi; Ma, Zhuo; Sun, Ximu; Feng, Xin; An, Zhuoling
Abstract: Background: Cyclin-Dependent Kinase (CDK) 4/6 inhibitors have shown significant clinical activity in cancer patients. However, some concerns regarding rare adverse events (AEs) have occurred including interstitial lung disease (ILD)/pneumonitis, for which data are deficient. The aim of this study was to evaluate the overall incidence and risk of ILD/pneumonitis related to CDK4/6 inhibitors in randomized controlled trials (RCTs). Methods: Electronic databases and ClinicalTrials.gov were searched from inception to October 1, 2021 for RCTs reporting the occurrence of LD/pneumonitis in cancer patients treated with CDK4/6 inhibitors. Peto odds ratios (Peto ORs) and 95% confidence intervals (CIs) were used to pool the study. Results: 12 RCTs with a total of 16, 060 patients were eligible. The overall incidence of all-grade ILD/pneumonitis was 1.6% (131/8407) in the treatment group compared with 0.7% (50/7349) in the control group. CDK4/6 inhibitors significantly increased the risk of all-grade ILD/pneumonitis with a pooled Peto OR of 2.12 (95% CI [1.57, 2.86], P < 0.00001) with no heterogeneity (I 2 = 0%, χ 2 P = 0.98). A higher incidence of grade 3 or higher ILD/pneumonitis was also observed in the treatment group (0.2%, 16/7087) compared with the control group (0.05%, 3/6617) with a Peto OR of 3.22 (95% CI [1.28, 8.09], P = 0.01) with no heterogeneity (I 2 = 0%, χ 2 P = 0.62). Two grade 5 pneumonitis were reported in the included studies. Subgroup analyses did not show any significant difference. Conclusions: The risk of all-grade and grade 3 or higher ILD/pneumonitis was higher in patients treated with CDK4/6 inhibitors compared to controls. The awareness for these rare AEs in the application of CDK4/6 inhibitors should be enhanced. Further studies are required to validate the mechanisms and the risk factors of ILD/pneumonitis with CDK4/6 inhibitors. Highlights: CDK4/6 inhibitors significantly increased the risk of all-grade ILD/pneumonitis. CDK4/6 inhibitors significantly increased the risk of grade ≥3 ILD/pneumonitis. Palbociclib and abemaciclib showed the most significant risk of ILD/pneumonitis. CDK4/6 inhibitor-related ILD/pneumonitis may lead to fatal outcomes.